Holistic analysis of lysine acetylation in aquaculture pathogenic bacteria Vibrio alginolyticus under bile salt stress - Xiao, Xing; Li, Wanxin; Pan, Yanfang; Wang, Junlin; Wei, Zhiqing; Wang, Shi; Wang, Na; Jian, Jichang; Pang, Huanying (Frontiers in Veterinary Science, 2023)
Lysine acetylation modification is a dynamic and reversible post-translational modification, which plays an important role in the metabolism and pathogenicity of pathogenic bacteria. Vibrio alginolyticus is a common pathogenic bacterium in aquaculture, and bile salt can trigger the expression of bacterial virulence. However, little is known about the function of lysine acetylation in V. alginolyticus under bile salt stress. In this study, 1315 acetylated peptides on 689 proteins were identified in V. alginolyticus under bile salt stress by acetyl-lysine antibody enrichment and high-resolution mass spectrometry. Bioinformatics analysis found that the peptides motif ****A*Kac**** and *******Kac****A* were highly conserved, and protein lysine acetylation was involved in regulating various cellular biological processes and maintaining the normal life activities of bacteria, such as ribosome, aminoacyl-tRNA biosynthesis, fatty acid metabolism, two-component system, and bacterial secretion system. Further, 22 acetylated proteins were also found to be related to the virulence of V. alginolyticus under bile salt stress through secretion system, chemotaxis and motility, and adherence. Finally, comparing un-treated and treated with bile salt stress lysine acetylated proteins, it was found that there were 240 overlapping proteins, and found amino sugar and nucleotide sugar metabolism, beta-Lactam resistance, fatty acid degradation, carbon metabolism, and microbial metabolism in diverse environments pathways were significantly enriched in bile salt stress alone. In conclusion, this study is a holistic analysis of lysine acetylation in V. alginolyticus under bile salt stress, especially many virulence factors have also acetylated.